Optimalisasi Peran Filantropi Islam dalam Meningkatkan Kesadaran Sosial Mahasiswa Program Studi Sosiologi - Indriana; Mohamad Agung Rokhimawan; Yayan Suryana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic philanthropy, which includes concepts such as infaq, sadaqah, and zakat, has great potential to be an effective tool in building students' social awareness. This study aims to examine the potential and effectiveness of optimizing the role of Islamic philanthropy in increasing the social awareness of students of the Sociology Study Program. Islamic philanthropy includes humanitarian values, social solidarity, and concern for the surrounding environment. This research uses qualitative methods with in-depth interviews, observation, and document analysis as data collection techniques. The research findings show that Islamic philanthropy has great potential to become an agent of change in increasing students' social awareness. In the context of the Sociology Study Program, the implementation of Islamic values in philanthropic activities can enrich students' understanding of social and humanitarian issues.